Imported malaria in children: A 13 years retrospective study. Issue 46 (March 2022) - Agagliati, Federica; Silvestro, Erika; Denina, Marco; Garazzino, Silvia; Mignone, Federica; Zoppo, Marisa; Pruccoli, Giulia; Scolfaro, Carlo
Abstract: Malaria is not endemic in Italy, however every year about 600-700 imported cases are detected in people born or living in Italy who return from a stay in their country of origin (visiting friends and relatives – VFR). Children account for 20% of this population and they have an higher risk of severe disease. Socio-economic problems and deficiencies in the doctor-patient relationship often lead to a lack of awareness of the importance of prophylaxis, making the category of VFRs at increased risk of disease. The aim of this study is to analyze the characteristics of pediatric imported malaria, with a specific focus on prevention and risk factors for severe malaria. All malaria cases diagnosed from 2007 to 2019 in Ospedale Infantile Regina Margherita in Turin were retrospectively observed. Epidemiological and clinical data were described. A total of 72 patients were reported: 98.6% had African origins and 73.6% traveled as VFRs. Plasmodium falciparum was the species most commonly isolated (94.4%). Twenty-four patients (33.3%) underwent chemoprophylaxis and never appropriately. Patients not undergoing prophylaxis and those undergoing incomplete prophylaxis showed not statistically significant difference in term of disease severity (p = 0.26). Nineteen cases were considered severe, including 3 with cerebral malaria. High levels of parasitemia were statistically significantly correlated with severe anemia (p = 0.049) and severe thrombocytopenia (p = 0.036). In 25% of cases the first diagnosis was incorrect. The therapeutic use of artemisinin derivatives has resulted in a significant shortening of the parasitemia clearance time compared to the use of other drugs (p < 0.001). Families have to be educated about the serious implications of a malaria infection and the importance of a correct and complete prophylaxis. Clinicians should always consider malaria in the differential diagnoses in patients with fever and a history of a recent travel to an endemic area. Prompt diagnosis and use of appropriate drugs, according to the latest guidelines, could guarantee a better outcome for patients.